Muraymycin nucleoside-peptide antibiotics: uridine-derived natural products as lead structures for the development of novel antibacterial agents - Wiegmann, Daniel; Koppermann, Stefan; Wirth, Marius; Niro, Giuliana; Leyerer, Kristin; Ducho, Christian (Beilstein Journal of Organic Chemistry, 2016)
Muraymycins are a promising class of antimicrobial natural products. These uridine-derived nucleoside-peptide antibiotics inhibit the bacterial membrane protein translocase I (MraY), a key enzyme in the intracellular part of peptidoglycan biosynthesis. This review describes the structures of naturally occurring muraymycins, their mode of action, synthetic access to muraymycins and their analogues, some structure–activity relationship (SAR) studies and first insights into muraymycin biosynthesis. It therefore provides an overview on the current state of research, as well as an outlook on possible future developments in this field.
Keywords: antibiotics; natural products; nucleosides; peptides; structure–activity relationship